Preparation and Thermal Characterization of Annealed Gold Coated Porous Silicon - Behzad, Kasra (Materials (Basel), 2012)
Porous silicon (PSi) layers were formed on a p-type Si wafer. Six samples were anodised electrically with a 30 mA/cm(2) fixed current density for different etching times. The samples were coated with a 50–60 nm gold layer and annealed at different temperatures under Ar flow. The morphology of the layers, before and after annealing, formed by this method was investigated by scanning electron microscopy (SEM). Photoacoustic spectroscopy (PAS) measurements were carried out to measure the thermal diffusivity (TD) of the PSi and Au/PSi samples. For the Au/PSi samples, the thermal diffusivity was measured before and after annealing to study the effect of annealing. Also to study the aging effect, a comparison was made between freshly annealed samples and samples 30 days after annealing.